Analisis Sistematis Perbandingan Kurikulum Fisika Sekolah Menengah di Berbagai Negara - Zahara, Laxmi; Lasmawan, I Wayan; Suharta, I Gusti Putu; Widiana, I Wayan (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This study conducts a systematic review of secondary school physics curricula in 18 countries, including both developed and developing nations, to identify patterns in curriculum structure, pedagogical approaches, and implemented innovations. Utilizing the PRISMA framework, 25 indexed articles published between 2020 and 2025 were analyzed using comparative and content analysis methods. The findings reveal significant differences in curriculum modularity and flexibility. Developed countries such as Finland, Germany, and the United States adopt highly adaptive and student-centered models, while developing countries like Pakistan and Rwanda implement more rigid and centralized models. Globally, there is a pedagogical shift towards inquiry-based learning, the integration of contextual and cultural values, and the use of innovative technologies such as PhET simulations, Arduino, Python, and digital assessment tools. This study highlights practical implications for Indonesia, emphasizing the need to implement a physics curriculum that is more flexible, contextual, and technologically innovative, while integrating local values to equip students with 21st-century competencies.